Efficient charge extraction and slow recombination in organic–inorganic perovskites capped with semiconducting single-walled carbon nanotubes. Issue 4 (23rd February 2016) - Ihly, Rachelle; Dowgiallo, Anne-Marie; Yang, Mengjin; Schulz, Philip; Stanton, Noah J.; Reid, Obadiah G.; Ferguson, Andrew J.; Zhu, Kai; Berry, Joseph J.; Blackburn, Jeffrey L.
Abstract : Capping perovskite absorber layers with semiconducting carbon nanotubes enables sub-picosecond hole extraction and recombination times of hundreds of microseconds. Abstract : Metal-halide based perovskite solar cells have rapidly emerged as a promising alternative to traditional inorganic and thin-film photovoltaics. Although charge transport layers are used on either side of perovskite absorber layers to extract photogenerated electrons and holes, the time scales for charge extraction and recombination are poorly understood. Ideal charge transport layers should facilitate large discrepancies between charge extraction and recombination rates. Here, we demonstrate that highly enriched semiconducting single-walled carbon nanotube (SWCNT) films enable rapid (sub-picosecond) hole extraction from a prototypical perovskite absorber layer and extremely slow back-transfer and recombination (hundreds of microseconds). The energetically narrow and distinct spectroscopic signatures for charges within these SWCNT thin films enables the unambiguous temporal tracking of each charge carrier with time-resolved spectroscopies covering many decades of time. The efficient hole extraction by the SWCNT layer also improves electron extraction by the compact titanium dioxide electron transport layer, which should reduce charge accumulation at each critical interface. Finally, we demonstrate that the use of thin interface layers of semiconducting single-walled carbon nanotubes between the perovskite absorber layer and a prototypical hole transport layer improves device efficiency and stability, and reduces hysteresis.